The role of neurotrophins in acute coronary syndrome prognostic and diagnostic value of new biomarkers - Sreckovic, Miodrag; Vojinović, Radiša; Kumburović, Davor (Medicinski časopis, 2025)
Acute coronary syndrome (ACS) remains a leading cause of morbidity and mortality worldwide. While existing diagnostic and prognostic biomarkers have improved patient care, there’s still a need for newer, more specific markers to enable more precise risk stratification and individualized treatment. Neurotrophins are a family of proteins essential for neuronal survival and function. In recent years, their role in cardiovascular diseases has become increasingly recognized. The aim of this review is to present current knowledge on the role of neurotrophins, primarily BDNF and NGF, in the pathophysiology of ACS, and to evaluate their potential as novel diagnostic and prognostic biomarkers. Analyzed studies indicate significant changes in neurotrophin levels during ACS, linking them to ischemia, reperfusion injury, inflammation, and myocardial remodeling. There’s evidence that elevated or decreased levels of certain neurotrophins can predict short-term and long-term outcomes in patients with ACS. Further research, especially large multicenter studies, is necessary to confirm the value of neurotrophin measurement in ACS as a significant biomarker in clinical practice.